METODE KUANTITATIF PADA ANALISIS KEBUTUHAN DIKLAT BIDANG MITIGASI BENCANA GEMPA BUMI - Aperta Ledy Alam (PPSDM Geominerba, 2017)
The use of quantitative methods for Training Needs Analysis (TNA) by using questionnaire instrument that contains statement of competency and is calculated by certain formulation can be a tool in mapping employees’ competency gap. This formulation-based calculation gives two main outcomes: mapping of competency gap category and competency gap among respondents. The classification of competency gap in TNA is divided into competencies with high and low scores. One of the final results of this research is recommendation of competency gap, and its mutual response with education and training, or other kinds of employee’s development programs.